PENGARUH PEMBELAJARAN MEDIA APLIKASI CANVA TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN SIMULASI DIGITAL - Lufy Fadilah; Eva Gustiana (Jurnal Bastra (Bahasa dan Sastra), 2026)
Student learning outcomes in the Digital Simulation subject at SMKN 1 Kuningan show suboptimal achievement due to the limitations of conventional learning media. To address this, this study examines the effectiveness of the Canva application as a visual technology-based learning medium. The literature review draws on visual learning theory and previous research, which confirms that digital media can improve student motivation and learning outcomes. The research method used was quantitative with a quasi-experimental design, namely a one-group pretest-posttest design. The subjects were grade 10 Agro 2 students selected using a purposive sampling technique. Data were collected through tests (pretest and posttest) and documentation, then analyzed statistically. The results showed a significant increase from an average pretest score of 60.50 to 80.41 on the posttest, a difference of 19.91 points. This demonstrates that the use of Canva has a positive and significant impact on student learning outcomes. Therefore, Canva can be used as an alternative, innovative, interactive learning medium relevant to the needs of vocational students, while also contributing to the development of technology-based learning media.